Global Country Classification of Sustainable Startups Levels - Bradač Hojnik, Barbara (Problemy Ekorozwoju, 2024)
In today’s world, the pursuit of sustainable development has become a global priority. However, the integration of sustainability practices in entrepreneurial ventures, particularly in new startups, lags behind. This article aims to bridge the gap between sustainable development and entrepreneurship by examining the role of sustainability in the formation of sustainable startups. Through the use of cluster analysis, this study classifies countries based on their environmental and social objectives in the context of sustainable startups. The analysis reveals distinct clusters of countries with varying degrees of emphasis on environmental and social considerations. The results of the analysis provide valuable insights into the distribution of countries across different clusters, delineating the sustainable goals of startups in those countries. These findings align with existing research on sustainable entrepreneurship and contribute to the broader discourse in the field. The implications of these findings are significant for promoting sustainable entrepreneurship. While the study acknowledges several limitations, future research can expand upon these findings to develop a more comprehensive understanding of sustainable entrepreneurship on a global scale.